Novel and Highly Potent Therapeutic Agent, Trametes Robiniophila Murr (Huaier), Mitigates Pulmonary Vascular Remodeling in Rodents - Huangshu Ye; Yue Zhang; Li Hu; Yuxin Feng; Tianfan Zhu; Qi Meng; Xiaoxuan Sun; Miaojia Zhang; Zhengsheng Mao; Feng Chen; Yanfang Yu; Qiang Wang; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Pulmonary hypertension (PH) is a critical disease causing right ventricular failure and early death. Conventional single‐pathway treatments are inadequate, highlighting the need for new therapies. Trametes robiniophila Murr (Huaier), a traditional Chinese medicine, inhibits cancer cell proliferation. Importantly, the aberrant proliferation of pulmonary artery smooth muscle cells (PASMCs) is a key contributor to increased pulmonary vascular resistance in PH. However, it remains unknown whether Huaier could protect against PH. This study aimed to examine whether Huaier could protect against PH as well as its underlying mechanisms. Methods Huaier treatment effectively mitigated hypoxia‐ and monocrotaline‐induced PH in rodent models, as evidenced by reductions in pulmonary artery pressure, right ventricular hypertrophy, and vascular remodeling. Transcriptomic and network pharmacology analyses suggested that Huaier effectively alleviates PH primarily through inhibiting the phenotypic switching of PASMCs. Results In vitro, Huaier suppressed PASMCs proliferation and migration in both PDGF (platelet‐derived growth factor)‐treated PASMCs and PH‐PASMCs. Mechanistically, Huaier treatment was found to significantly inhibit the Hif1α (hypoxia‐inducible factor 1‐alpha) signaling pathway, thereby reducing excessive lactate accumulation and abnormal glycolysis, and the NF‐κB (nuclear factor κB) signaling pathway, thereby diminishing inflammatory responses. Additionally, Huaier activated the Nrf2 (nuclear factor erythroid 2‐related factor 2) signaling pathway, enhancing mitochondrial function and alleviating oxidative stress. The multifunctional roles of Huaier contributed to its inhibited effect on PASMCs proliferation and thus improved vascular remodeling. Conclusions Huaier exerts multitarget therapeutic effects against PH by concurrently modulating metabolic reprogramming, inflammation and oxidative homeostasis, thereby inhibiting PASMCs‐driven vascular remodeling. These findings position Huaier as a promising candidate for PH treatment, warranting further clinical trials to validate its translational potential.